Building Development In The Tod Jakarta Area In The Form Of Increasing The Floor Coefficient Of Integrated Mixed Buildings With All MRT Busway LRT Facilities In The Pulomas Area, East Jakarta - Kamaruzzaman Onaning; Uras Siahaan; Yopie Yopie (Journal of Social Research, 2024)
The development of Transit-Oriented Areas (TOD) has been established provisions and regulations related to the requirements and rules of implementation through the Minister of Agrarian Regulation number 16 of 2017 and DKI Jakarta Governor Regulation number 67 of 2019. Submission of an area for the TOD Area can be submitted by the landowning community to the Governor of the DKI Jakarta Provincial Government, it is also possible to cooperate with BUMN or BUMD which have obtained the right to manage the TOD Area from the Governor of DKI Jakarta Province. TOD Areas that are integrated with the Public Transport System will have a positive impact on the Community, in the form of transportation cost efficiency, ease of reaching the terminal location, equipped with pedestrian and cycling facilities. With the increasing need for land, especially around Mass Public Transport Facilities, incentives are given in the form of an increase in the Building Floor Area Coefficient (KLB) in the TOD Area according to the established TOD typology. Regulations regarding the increase of Building Floor Area Coefficient in TOD Area along with the procedure and the amount of incentives obtained are regulated in Governor Regulation number 31 of 2022. TOD areas that are integrated with Public Transport Facilities will improve the quality of urban space utilisation, increase property values by involving stakeholders.